A model of lecturers\ power motivation, empowerment, perceived inequality, internal service quality and burnout to students satisfaction - Mohamad Yusof Abdul Raheem, Yeop Yunus Nek Kamal, Mujahid Ghouri Arsalan, (Universiti Pendidikan Sultan Idris, 2012)
A model of lecturers\ power motivation, empowerment, perceived inequality, internal service quality and burnout to students satisfaction by Mohamad Yusof Abdul Raheem, Yeop Yunus Nek Kamal, Mujahid Ghouri Arsalan,